A Mini Review of Antibacterial Properties of ZnO Nanoparticles - Gudkov, Sergey V.; Burmistrov, Dmitriy E.; Serov, Dmitriy A.; Rebezov, Maxim B.; Semenova, Anastasia A.; Lisitsyn, Andrey B. (Frontiers in Physics, 2021)
The development of antibiotic resistance of bacteria is one of the most pressing problems in world health care. One of the promising ways to overcome microbial resistance to antibiotics is the use of metal nanoparticles and their oxides. In particular, numerous studies have shown the high antibacterial potential of zinc oxide nanoparticles (ZnO-NP) in relation to gram-positive and gram-negative bacteria. This mini-review includes an analysis of the results of studies in recent years aimed at studying the antibacterial activity of nanoparticles based on zinc oxide. The dependence of the antibacterial effect on the size of the applied nanoparticles in relation to E. coli and S. aureus is given. The influence of various ways of synthesis of zinc oxide nanoparticles and the main types of modifications of NP-ZnO to increase the antibacterial efficiency are also considered.